Fatal forførelse: Retorisk-etisk narratologi og Olivia Levisons »Loreley« - Rosiek, Jan (Danske Studier, 2024)
This essay studies the ethical dimensions of James Phelan’s rhetorical reading strategy. Briefly demarcating Phelan’s differences from two other positions within literary ethics, Martha Nussbaum’s and Judith Butler’s, it proceeds to a critical discussion of his typology of four audiences (flesh-and-blood readers, narrative audience, authorial audience, narratee), four ethical positions (character, narrator, implied author, rhetorical flesh-and-blood reader) and four thematic issues (the told, the telling, writing/producing, reception), paying particular attention to the concept of judgment and its status and function in ethical readings. Referring to Per Krogh Hansen’s characterology, the essay presents a Phelan-inspired ethical reading of Olivia Levison’s »Loreley« (1877), a story of a triangle between the narrator, his friend Bergarén and miss Harder, the eponymous protagonist. Focusing on the judgments of the three main characters, it argues that the narrator is unreliable and that the text suggests another understanding of miss Harder than the two male protagonists’ conviction that she is a dangerously seductive femme fatale. The essay also comments on the inadequate reception history of Levison’s story and its relevance for current discussions on the rules of interaction between the sexes.